An Independent Scholar: Lawrence Moonan's Legacy. (29th July 2014) - Kerr, Fergus
Abstract Lawrence Moonan (1937–2013) pioneered the study of the medieval Scottish philosopher Lawrence of Lindores; he published a major work on the notion of divine omnipotence in early scholasticism; and he kept worrying that in these post‐Deistical times many philosophers and theologians have forgotten what it is like to think of God as strictly infinite.